Sex estimation from human dentition: forensic odontology techniques and applications - Acharya, Neha; Babu, N. Arvindha (International Journal Of Community Medicine And Public Health, 2025)
Sex determination is an intrinsic part of forensic identification since it eliminates half of the potential matches, thus increasing accuracy in situations such as mass disasters, criminal investigations and analysis of shattered or decomposed remains. Forensic odontology has been a very strong branch in this sense, attributable mainly to the outstanding resistance of dental tissues to post-mortem insults like trauma, fire and extended submersion. A range of methodological approaches has been employed for sex estimation from dental evidence, encompassing morphological, odontometric, molecular and technologically advanced modalities. Odontometric measurements, notably the mandibular canine index, crown and root dimensions and dental arch characteristics, demonstrate consistent dimorphic trends. Morphological indicators such as shovel-shaped incisors, Carabelli’s cusp and palatal rugae further contribute to biological profiling. The use of radiographic methods, such as orthopantomograms (OPGs), cone-beam computed tomography (CBCT) and micro-computed tomography, enables accurate visualization of sexually dimorphic dental and craniofacial morphology. Molecular markers, such as Amelogenin, SRY and DYS14, offer genetic pathways for sexing, especially in highly degraded remains. Newly developing artificial intelligence and machine learning techniques offer the potential for increased efficiency and predictive precision. Future progress requires standardized guidelines, population-based data sets and cross-disciplinary coordination to maintain forensic odontology as a scientifically sound instrument in personal identification.